2017
DOI: 10.1038/s41598-017-18018-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mechanical Twinning in Magnesium Silicate Post-Perovskite

Abstract: The plastic properties of MgSiO3 post-perovskite are considered to be one of the key issues necessary for understanding the seismic anisotropy at the bottom of the mantle in the so-called D” layer. Although plastic slip in MgSiO3 post-perovskite has attracted considerable attention, the twinning mechanism has not been addressed, despite some experimental evidence from low-pressure analogues. On the basis of a numerical mechanical model, we present a twin nucleation model for post-perovskite involving the emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…High-resolution TEM images further revealed that the nanocrystallites contain many stacking faults (SFs) produced by slipping of lattice planes under external compression (Figure 3c). 38 Similar observations hold for the senary sample (Figure 3d−f). These facts suggest that the applied external high pressure caused abundant nanocracking in the sample grains, which turned the initially micrometer-sized (bulk) sample into nanocrystallites with many SFs.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…High-resolution TEM images further revealed that the nanocrystallites contain many stacking faults (SFs) produced by slipping of lattice planes under external compression (Figure 3c). 38 Similar observations hold for the senary sample (Figure 3d−f). These facts suggest that the applied external high pressure caused abundant nanocracking in the sample grains, which turned the initially micrometer-sized (bulk) sample into nanocrystallites with many SFs.…”
supporting
confidence: 68%
“…There are many nanosized cracks with widths of ∼1–10 nm lying between the nanocrystallite boundaries (as indicated by the arrows in Figure b). High-resolution TEM images further revealed that the nanocrystallites contain many stacking faults (SFs) produced by slipping of lattice planes under external compression (Figure c) . Similar observations hold for the senary sample (Figure d–f).…”
supporting
confidence: 61%
“…This shear wave splitting can be used to characterize mantle strain fields, which in turn allows for mantle structures to be observed (Savage, 1999). There are many regions within the lower mantle, past 1000 km, that are seismically isotropic (Panning and Romanowicz, 2006;Beghein et al, 2006) even though numerous experimental studies demonstrate lowermantle phases of bridgmanite and ferropericlase are highly anisotropic and even increase in anisotropy with depth (Chen et al, 1998;Mainprice et al, 2000). In the case of the D region, where a phase transformation from perovskite to postperovskite could take place (Murakami et al, 2004;Hernlund et al, 2005;Koelemeijer et al, 2018), strong anisotropy is observed (Garnero et al, 2004;Panning and Romanowicz, 2006;Wookey and Kendall, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The deformation behavior of bridgmanite (Cordier et al., 2004; Merkel et al., 2003; Miyagi & Wenk, 2016; Tsujino et al., 2016; Wenk et al., 2004), davemaoite (Immoor et al., 2022; Miyagi et al., 2009), and ferropericlase (Immoor et al., 2018; Merkel et al., 2002; Miyagi & Wenk, 2016) have been investigated under high pressures and, sometimes, high temperatures. These experiments have helped in constraining plasticity and deformation mechanisms in minerals (Cordier et al., 2004; Miyagi et al., 2010; Miyajima et al., 2009) with the addition of numerical models, allowing for studies on the effects of composition, temperature, and strain rate (Boioli et al., 2017; Carrez et al., 2007, 2017; Ferré et al., 2007; Mainprice et al., 2008) that cannot be addressed experimentally. Those, however, were not performed on a true pyrolitic composition, nor both at mantle pressures and temperatures and deserve a new investigation.…”
Section: Introductionmentioning
confidence: 99%